2022
DOI: 10.1111/iej.13822
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of root canal treatment worldwide: A systematic review and meta‐analysis

Abstract: Background:The prevalence of root filled teeth (RFT) worldwide will inform about the amount of clinical activity of dentists dedicated to treat endodontic disease.Objectives: To carry out a systematic review with meta-analysis answering the following question: What is the prevalence of RFT around the world? The percentage of people with at least one RFT was also investigated.Methods: A systematic review including population-based studies using the following databases: PubMed, EMBASE and Scielo. Studies related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 116 publications
4
33
0
Order By: Relevance
“…Still, despite the disadvantages related to the undesirable superimposition of anatomical structures, panoramic radiographs are useful for assessing the patients' overall dental health and for detecting periapical lesions 26 . These observations are confirmed by the findings of a recent systematic literature review indicating that majority of studies in this domain were based on panoramic radiographs, allowing their results to be compared and contrasted, which increases their external validity 27 .…”
Section: Discussionsupporting
confidence: 72%
“…Still, despite the disadvantages related to the undesirable superimposition of anatomical structures, panoramic radiographs are useful for assessing the patients' overall dental health and for detecting periapical lesions 26 . These observations are confirmed by the findings of a recent systematic literature review indicating that majority of studies in this domain were based on panoramic radiographs, allowing their results to be compared and contrasted, which increases their external validity 27 .…”
Section: Discussionsupporting
confidence: 72%
“…Nowadays the main clinical treatment is root canal therapy (RCT) which involves the extirpation of the entire dental pulp and filling with an artificial material, resulting in a higher incidence of extraction. However, teeth after RCT are susceptible to fracture and more prone to mechanical damage, resulting in a higher incidence of extraction [3][4][5]. Recently, mesenchymal stem cell-(MSC-) based tissue engineering has shown immense potential for dental pulp regeneration, which was proposed as an alternative to conventional endodontic treatment [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Root canal treatments are performed to prevent or treat AP; however, it has been observed that a higher frequency of root filled teeth have AP compared to non-root filled teeth. It has been reported that 50% of the adult population globally has at least one root filled tooth and the global frequency of root fillings (RFs) is almost 10% (León-López et al, 2022). Increased tooth retention in ageing population may increase the proportion of root filled teeth (Kirkevang, 2018a).…”
Section: Introductionmentioning
confidence: 99%